Legio XX Valeria Victrix: a prosopographical and historical study - Malone, Stephen James (2005)
This study of legio XX Valeria Victrix combines a prosopographical and historical approach to the study of the legion as a whole. Epigraphic and historical evidence is presented for all those individuals known to have served with the Twentieth Legion in their various capacities. Sources are quoted, with translation, for each of these and significant details of the careers discussed. Further aspects of careers generally are considered at the end of the relevant sections. This corpus is supported by a number of indices - of nomenclature, origins, ranks, service and posts held in other units etc., as well as an index of primary sources. Other inscriptions attesting to the presence of the Twentieth legion and its activities in various quarters of the Empire are also collected and presented. This epigraphic evidence is drawn together with that of the archaeological and historical sources, along with the copious modem literature on the subject of the Roman Army, to present a history of the Twentieth Legion from its formation out of the legions of the civil wars of the late Republic, to its uncertain end in the changing conditions of the late third and fourth centuries. Particular emphasis is placed on the role of individuals and the light that their careers can shed on the history and activities of the legion. Studies on a number of other aspects of the history and organisation of the legion are appended.